BAURAN PEMASARAN BUAH DI TOKO BUAH EWI KECAMATAN SUMBAWA - Kamasdianti Kamasdianti; Alia Wartiningsih; Lukman Hakim; Siti Nurwahidah; Yadi Hartono (JURNAL SOSIAL EKONOMI PERTANIAN, 2026)
This study aimed to analyze the marketing mix implemented by Ewi Fruit Store in Sumbawa District. The research was conducted in April 2025. The study location was selected purposively, while respondents were chosen using an accidental sampling technique. A descriptive research method was employed, involving 30 consumers who purchased fruit at Ewi Fruit Store. Data were analyzed using the Likert scale. The results showed that the store implemented the marketing mix through a variety of strategies. In terms of product, the store offered a wide range of local and imported fruits, with some products packaged using plastic wrapping, clamshell boxes, and foam nets. Pricing was determined based on market prices and adjusted according to the type, quality, size, and packaging of the fruit. The store was strategically located and easily accessible to customers. Promotional activities included the use of banners, word-of-mouth marketing, and social media. Employees provided friendly, polite, neat, and responsive customer service. The service process included product selection, weighing, payment, and packaging. Physical evidence consisted of a clean and well-organized store, supported by facilities such as weighing scales and air conditioning. Consumer responses indicated that all elements of the marketing mix were rated very good, with average scores of 22.27 for product, 22.23 for price, 23.20 for place, 21.10 for promotion, 22.17 for people, 23.17 for process, and 21.67 for physical evidence. These findings indicate that the marketing mix implemented by Ewi Fruit Store has been highly effective.